The Identification of Interferon-γ as a Key Supportive Factor for Retinal Differentiation of Murine Mesenchymal Stem Cells - Hermankova, Barbora; Kossl, Jan; Javorkova, Eliska; Bohacova, Pavla; Hajkova, Michaela; Zajicova, Alena; Krulova, Magdalena; Holan, Vladimir (Stem cells and development, 2017)
Retinal disorders represent the main cause of decreased quality of vision and even blindness worldwide. The loss of retinal cells causes irreversible damage of the retina, and there are currently no effective treatment protocols for most retinal degenerative diseases. A promising approach for the treatment of retinal disorders is represented by stem cell-based therapy. The perspective candidates are mesenchymal stem cells (MSCs), which can differentiate into multiple cell types and produce a number of trophic and growth factors. In this study, we show the potential of murine bone marrow-derived MSCs to differentiate into cells expressing retinal markers and we identify the key supportive role of interferon-γ (IFN-γ) in the differentiation process. MSCs were cultured for 7 days with retinal extract and supernatant from T-cell mitogen concanavalin A-stimulated splenocytes, simulating the inflammatory site of retinal damage. MSCs cultured in such conditions differentiated to the cells expressing retinal cell markers such as rhodopsin, S antigen, retinaldehyde-binding protein, calbindin 2, recoverin, and retinal pigment epithelium 65. To identify a supportive molecule in the supernatants from activated spleen cells, MSCs were cultured with retinal extract in the presence of various T-cell cytokines. The expression of retinal markers was enhanced only in the presence of IFN-γ, and the supportive role of spleen cell supernatants was abrogated with the neutralization antibody anti-IFN-γ. In addition, differentiated MSCs were able to express a number of neurotrophic factors, which are important for retinal regeneration. Taken together, the results show that MSCs can differentiate into cells expressing retinal markers and that this differentiation process is supported by IFN-γ.
Keywords: interferon gama; Interferon-gamma; kultivované buňky; Mice, Inbred BALB C; neurotrophic factor; Cell Differentiation; rhodopsin; Recoverin; Carrier Proteins; differentiation; kalbindin 2; Mesenchymal Stem Cells; Mice; retina; mesenchymal stem cell; cis-trans-Isomerases; Cells, Cultured; mezenchymální kmenové buňky; Retina; ženské pohlaví; zvířata; Rhodopsin; Calbindin 2; myši inbrední BALB C; cis-trans-isomerasy; interferon-γ; myši; rekoverin; rodopsin; buněčná diferenciace; Female; transportní proteiny; Animals